2013
DOI: 10.1021/mp400539r
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Amphiphile Containing Arginine and Fatty Acyl Chains as Molecular Transporters

Abstract: Peptide amphiphiles (PAs) are promising tools for the intracellular delivery of numerous drugs. PAs are known to be biodegradable systems. Here, four PA derivatives containing arginine and lysine conjugated with fatty acyl groups with different chain length, namely PA1: R-K(C14)-R, PA2: R-K(C16)-R, PA3: K(C14)-R-K(C14), and PA4: K(C16)-R-K(C16), where C16 = palmitic acid and C14 = myristic acid, were synthesized through Fmoc chemistry. Flow cytometry studies showed that among all synthesized PAs, only K(C16)-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…(A) The lipopeptide stearyl‐tetraarginine has been studied by Burlina et al for the covalent delivery of small cationic peptides . (B) Short cationic LPA containing one arginine and two lysines conjugated with palmitic acid were developed by Shirazi et al . (C) Oh et al prepared a cyclic dodecanoyl‐[Arg6] LPA for the non‐covalent delivery of small anionic phosphopeptides .…”
Section: Modification Of the Structure Of Acylated Arginine‐rich Cppsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) The lipopeptide stearyl‐tetraarginine has been studied by Burlina et al for the covalent delivery of small cationic peptides . (B) Short cationic LPA containing one arginine and two lysines conjugated with palmitic acid were developed by Shirazi et al . (C) Oh et al prepared a cyclic dodecanoyl‐[Arg6] LPA for the non‐covalent delivery of small anionic phosphopeptides .…”
Section: Modification Of the Structure Of Acylated Arginine‐rich Cppsmentioning
confidence: 99%
“…They showed that an LPA containing one arginine and two lysines acylated by two palmitoyl acyl chains was able deliver into the cytoplasm a fluorescently labeled drug and a phosphopeptide. The endocytotic traffic was hypothesized to be the major internalization pathway .…”
Section: Modification Of the Structure Of Acylated Arginine‐rich Cppsmentioning
confidence: 99%
“…The loading efficiency experiment was conducted as described previosuly. 42 Aqueous solution of Dox (100 μL of 200 μM) was mixed with the solution of [W 5 R 4 C]–SeNPs in water (400 μL of 500 μM) to maintain a 1 to 10 molar ratio. After 24 h of incubation, the free Dox was collected by using the dialysis method.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the entrapment of the drugs was also carried out by using our previously reported procedure. 42 All assays were conducted in triplicate assays.…”
Section: Methodsmentioning
confidence: 99%
“…It was discovered that the presence of both arginine and tryptophan amino acids were critical to the function of the carrier system. Further investigations showed that, although the number of amino acids was important to maximize the transporting ability of the peptide, an optimized balance between electrostatic and hydrophobic forces are crucial for their high yield of intracellular uptake into cells [ 2 , 6 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%